2019
DOI: 10.1097/aog.0000000000003285
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Morbidity Associated With Early Term Delivery of Large-for-Gestational-Age But Nonmacrosomic Neonates

Abstract: To evaluate whether, at 37-39 weeks of gestation, delivery of a neonate with a birth weight that is 90% or greater for gestational age but less than 4,000 g is associated with increased composite maternal and neonatal morbidity. METHODS:This retrospective cohort study used U.S. Vital Statistics datasets for the years 2011-2013. Inclusion criteria were singleton pregnancies delivered at 37-39 weeks of gestation after labor in which the neonates were nonanomalous, and either appropriate for gestational age or la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 21 publications
(26 reference statements)
0
35
0
2
Order By: Relevance
“…Epidemiological data indicate that adverse pregnancy outcomes and pregnancy complications, including preterm births, preeclampsia (PE), gestational diabetes, and fetal growth restriction (IUGR), occur in total in up to 25% of first pregnancies [1] and these pregnancy results are an important element of public health. They are associated with an increase in maternal and fetal morbidity and/or mortality [2][3][4][5][6][7][8][9][10] and they may lead to long-term diseases of both the mother and the child, increasing the risk of cardiovascular diseases, obesity, diabetes, and even some cancers, as well as neurodevelopmental disorders in the offspring [7][8][9][10][11]. Early identification of women at risk may be of great importance for improving pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data indicate that adverse pregnancy outcomes and pregnancy complications, including preterm births, preeclampsia (PE), gestational diabetes, and fetal growth restriction (IUGR), occur in total in up to 25% of first pregnancies [1] and these pregnancy results are an important element of public health. They are associated with an increase in maternal and fetal morbidity and/or mortality [2][3][4][5][6][7][8][9][10] and they may lead to long-term diseases of both the mother and the child, increasing the risk of cardiovascular diseases, obesity, diabetes, and even some cancers, as well as neurodevelopmental disorders in the offspring [7][8][9][10][11]. Early identification of women at risk may be of great importance for improving pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, data comparing the cumulative live birth rates and the time to obtain a live child between the fresh and the freeze-all strategy are lacking. Furthermore, although the current literature supports the notion that freeze-all strategy is safe, particularly in light of the decreased risks of SGA and LBW, the data reveal higher rates of LGA/HBW and HDP, which are a reason for concern as these complications are associated with increased risks of adverse neonatal outcomes (Doty et al, 2019;Khambalia et al, 2017). There is also a paucity of information regarding rare obstetric/perinatal outcomes and childhood outcomes.…”
Section: Resultsmentioning
confidence: 82%
“…Of 3 917 831 births, only 50 630 (1,3 %) was non-macrosomic LGA. Authors concluded that non-macrosomic LGA had a greater risk of combined neonatal (aOR 1,47) and maternal (aOR 1,40) morbidity including a higher risk of maternal transfusion, maternal unplanned operating room procedures, need of assisted ventilation of neonate, fetal significant birth injury, or Apgar score <5 at 5 minutes [45].…”
Section: Shoulder Dystocia Oasis Pphmentioning
confidence: 99%